2008
DOI: 10.4049/jimmunol.180.1.79
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Tat Suppresses gp120-Specific T Cell Response in IL-10-Dependent Manner

Abstract: A large number of multicomponent vaccine candidates are currently in clinical evaluation, many of which also include the HIV-1 Tat protein, an important regulatory protein of the virus. However, whether Tat, a known immune effector molecule with a well-conserved sequence among different HIV subtypes, affects the immune response to a coimmunogen is not well understood. In this study, using a bicistronic vector expressing both gp120 and Tat, we have analyzed the role of Tat in elicitation of the gp120-specific i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 60 publications
(47 reference statements)
1
24
0
Order By: Relevance
“…At present, the reasons for these different results are not completely understood and require further investigation. One possible explanation for these different results may depend on the fact that in the studies [215,216] T cell responses directed against Env were searched using only a few Envderived peptides, which are not representative of the whole Env antigen, as opposite to our studies where sets of peptides representing the full-length Gag, Env, or with V2-deleted Env proteins were employed. Alternatively, differences in the vaccine formulation and immunization protocol may possibly account for these diverse results.…”
Section: Immunomodulatory Activity Of Hiv-1 Tatmentioning
confidence: 52%
See 1 more Smart Citation
“…At present, the reasons for these different results are not completely understood and require further investigation. One possible explanation for these different results may depend on the fact that in the studies [215,216] T cell responses directed against Env were searched using only a few Envderived peptides, which are not representative of the whole Env antigen, as opposite to our studies where sets of peptides representing the full-length Gag, Env, or with V2-deleted Env proteins were employed. Alternatively, differences in the vaccine formulation and immunization protocol may possibly account for these diverse results.…”
Section: Immunomodulatory Activity Of Hiv-1 Tatmentioning
confidence: 52%
“…In contrast with these results, using a DNA vaccination approach Agwale and co-worker reported that vaccination with a bi-cistronic gp120-tat DNA diminished IFN-γ CD8+ T cell responses against the immunodominant HIV-1 gp120 Env peptide in mice compared to those induced by vaccination with DNA encoding gp120 alone and that the effect of Tat was abolished by a sequence deletion (aa 31-50) in the cys-core domain of Tat (2). Morevoer, using a DNA vaccination approach, Gupta and co-workers [215] reported that vaccination with tat DNA in combination with env DNA inhibited T cell responses against Env through Tat-mediated induction of IL10. At present, the reasons for these different results are not completely understood and require further investigation.…”
Section: Immunomodulatory Activity Of Hiv-1 Tatmentioning
confidence: 99%
“…The suppression of DC maturation might benefit HIV-1 during the establishment of infection, as a suboptimal maturation of the cell decreases the likelihood of a potent HIV-1 targeted immune response (59,62). Our data suggest that HIV-1-infected DCs have a diminished capacity to activate naive T cells, because maturation is an essential prerequisite for T cell stimulation by DCs.…”
Section: Discussionmentioning
confidence: 78%
“…Several mechanisms are proposed, including the induction of IDO by Tat, which inhibits the capacity to activate T cells and the upregulation of the inhibitory protein PD-L1 (55,56,(58)(59)(60). The mechanism by which Vpr influences DC function remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the lack of a signal peptide, the Tat protein can be secreted by infected cells and taken up by neighboring cells, whether they are infected or not. Then, by its intracellular and cell surface actions, Tat may lead to HIV-1 transactivation in latently infected cells and to the activation or inhibition of a variety of cellular host factors, including proinflammatory cytokines and immunosuppressive factors known for their involvement in immune dysregulation (23,24,35), neurocognitive disorders (4), and intestinal glucose absorption dysfunctions (53). In association with the inflammatory response, the latter dysfunctions may contribute to the early alteration of the intestinal barrier observed in HIV-1-infected patients.…”
Section: Discussionmentioning
confidence: 99%